Enhanced osteoblast adhesion on amino-functionalized titanium surfaces through combined plasma enhanced chemical vapor deposition (PECVD) method. Issue 86 (31st August 2016) - Lu, Mengmeng; Shao, Dan; Wang, Ping; Chen, Danying; Zhang, Yidi; Li, Mingqiang; Zhao, Jinghui; Zhou, Yanmin
Abstract : A combined PECVD method has been developed to introduce amino-groups onto titanium implants for the better improvement of osseointegration. Abstract : Surface modification of titanium and its alloys with positively charged amino-groups has been proved to improve the performance of implants on initial osteoblast function. As a novel chemical approach, plasma enhanced chemical vapor deposition is now applied to introducing bioactive molecules to titanium surfaces with its own advantages. However, there is still little information about the effect of the combined plasma polymerization mode of plasma enhanced chemical vapor deposition on osseointegration of titanium surfaces. In this work, we aim to investigate the effect and mechanism of osteoblast adhesion on amino-functionalized titanium surfaces produced by different plasma polymerization modes of plasma enhanced chemical vapor deposition. The surface morphology and chemistry of these alloys were examined by scanning electron microscopy, scanning probe microscopy and X-ray photoelectron spectroscopy. CCK-8 assay, DAPI staining and flow cytometry showed that all amino-modified surfaces significantly induced osteoblast adhesion compared with pure titanium surfaces without any cytotoxicity. Immunofluorescence staining and western blotting further demonstrated a remarkable elevation of focal adhesion kinase phosphorylation with the increase of integrin α2 . More importantly, combined mode (CW + P) mediated surfaces possessed the best improvement of osseointegration. Taken together, our results indicate that amino-functionalizated titanium surfaces promote osteoblast adhesion through upregulation of integrin α2 and p-phosphorylated focal adhesion kinase. These findings will shed some light on the potential of combined plasma enhanced chemical vapor deposition methods for achieving ideal osseointegration on titanium surfaces.